2019
DOI: 10.1038/s41438-019-0133-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of interstock-induced dwarfism in Sweet Persimmon (Diospyros kaki Thunb.)

Abstract: Growth monitoring indicated that the height of ‘Kanshu’ plants with ‘Nantong-xiaofangshi’ as an interstock was significantly shorter than that of ‘Kanshu’ plants with no interstock. A transcriptome analysis of the two graft combinations (‘Kanshu’/ Diospyros lotus and ‘Kanshu’/‘Nantong-xiaofangshi’/ Diospyros lotus ) was conducted to explore the dwarfing genes related to the use of the ‘Nantong-xiaofangshi’ interstock. Hormone levels and water conductance were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 85 publications
1
16
0
2
Order By: Relevance
“…Of the two GA catabolic genes, AaGA2ox1 and AaGA2ox2, a more consistent increase in the transcript levels of the major gene, AaGA2ox1, in the period suggests an upregulation of GA deactivation in scion stems on marang rootstocks in this period (Figure 2). Upregulation of a GA2ox gene accompanying a decreased GA level was previously reported in scions of persimmon trees grafted on dwarfing interstocks [15]. Overexpression of GA2ox enhances GA deactivation and produces dwarf phenotype in many species [16,17,21].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Of the two GA catabolic genes, AaGA2ox1 and AaGA2ox2, a more consistent increase in the transcript levels of the major gene, AaGA2ox1, in the period suggests an upregulation of GA deactivation in scion stems on marang rootstocks in this period (Figure 2). Upregulation of a GA2ox gene accompanying a decreased GA level was previously reported in scions of persimmon trees grafted on dwarfing interstocks [15]. Overexpression of GA2ox enhances GA deactivation and produces dwarf phenotype in many species [16,17,21].…”
Section: Discussionmentioning
confidence: 65%
“…In ungrafted apple rootstocks, the level of GAs is the lowest in the dwarfing rootstock M.9 and the highest in the non-dwarfing rootstock MM111 [13]. Transcriptomic analysis revealed downregulation of GA biosynthetic genes in scions of apple trees gowning on dwarfing rootstocks [14] and upregulation of a GA catabolic gene together with decreased GA level in persimmon scion stems grafted on dwarfing interstocks [15]. Furthermore, a dwarf plum hybrid with elevated transcript levels of a major GA catabolic gene, GA2ox, exhibits shorter internodes and reduced stem elongation, and when used as rootstocks, it reduces the level of bioactive GAs in scions and reduces scion vigor [16].…”
Section: Introductionmentioning
confidence: 97%
“…In the present study, two-year-old “Nantongxiaofangshi” and “Dafangshi” scions grafted on “Junqianzi” rootstocks were obtained from the Fruit Tree Biotechnology Laboratory, Nanjing, China. The leaves sampled from “Nantongxiaofangshi” were taken at the leaf-expanding stage (2018.4.18), the terminal bud senescence stage (2018.5.10), the flowering stage (2018.5.22), the physiological fruit drop stage (2018.6.11), and the fruit color development stage (2018.9.13) [20]. All chemicals used in the present work were purchased from Beijing Solarbio Science and Technology Company Limited (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Deguchi et al have reported that a cDNA encoding sorbitol-6-phosphate dehydrogenase (S6PDH) of sorbitol biosynthesis from rosaceae was introduced into the Japanese persimmon ( Diospyros kaki ) to increase the environmental stress tolerance and exhibited dwarfing phenotypes [19]. According to our previous research reported, the “Nantongxiaofangshi” interstock has superior characteristic compared to the nongrafted persimmon trees [20]. Academic researches have mainly conducted on fruit trees, such as apple [21], pear [22], and citrus [23].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it must be taken into account that only relative quantification of the phloem sap can be performed since it is an exudation rather than a direct collection of the phloem sap [18]. New omics approaches have recently been applied in grafting studies to dissect the molecular mechanisms of the early graft-junction formation [20], to unveil the phenomenon of graft compatibility [21][22][23], and to understand the scion-rootstock interactions leading to the alteration of agronomically important traits [24][25][26]. Metabolites, as the end-product of gene expression and regulation, have also been investigated in grafted grapevine [27] and citrus trees [17] and were associated to graft formation and fruit quality.…”
Section: Introductionmentioning
confidence: 99%